A contextual approach on the views of muslim feminist interpreters of the Qur'on regarding women and their rights in the society . - Ali, Md. Yousuf (International Journal of Arts and Sciences, 2010)
The interpretation of the verses of the Qur’Én regarding women’s rights, role, and leadership is a challenge and much debatable subject. In Islam, the Qur’Én is seen by almost all Muslims as the words of Allah (swt). The majority Muslim exegetes interpreted the verses of the Qur’Én by applying a method of literal reading. In modern context, Muslim feminist interpreters of the Qur’Én have applied contextual and historical reading of the Qur’Én toward understanding women’s rights and leadership, which engrosses reading a verse with regard to the historical, social, and political context in which the verses were revealed. This approach aims to liberate Muslims from a literal reading of the Qur’Én and to liberalize Muslims from stringency with regard to basic human rights and equality between men and women, which articulate the values of a true Islam. Such approach is supported by many modern Muslim scholars. However, by applying this method, Muslim feminists face a great challenge and accusation from traditional Muslim exegetes. The accusation is that feminist scholarship is not loyal to the teachings of Islam and denies its heritage, which is the contribution of a male domain experiences. Such approach also produces liberal Islam and liberal Shar’ÊÑah, influenced by the Western values and imposed upon Islam and Muslims as believed by anti-feminists. The article focuses on how the method of contextualization is applied to some contentious verses in the Qur’Én, which discuss women’s rights and their roles in the society. Two questions on the basis of those verses will be examined; one is the question of men’s authority over women and the other is woman’s leadership in modern context. For instances, the contentious verse 4:34 recognizes man’s authority and superiority over woman for certain tasks and the verse 9:71 also recognizes the sovereign power of women ‘al-WilÉyah al-Mutlaqah’ equally in participating nation-building. We examine how two contemporary feminists Muslim thinkers; Fatima Mernissi, a Moroccan sociologist and Aminah Wadud Muhsin, an African-American professor of Islamic Studies use the hermeneutical method of contextual reading to interpret the texts of the Qur’Én. The article also evaluates the theoretical and practical challenges faced by them from traditional exegetes and argues that whether such a methodology strengthens their arguments and establishes woman’s rights and their roles in society? It is also argued that through the interpretation of the contextualization one may find difference with the previous interpretation of the Qur’Én, which is central to feminists exegesis.